1973
DOI: 10.1017/s0021859600058032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding water-soaked and dry wheat straw on feed intake, digestibility of nutrients and VFA production in growing zebu and buffalo calves

Abstract: Experiments were conducted on 12 male growing calves of zebu cattle {Bos indicus) and buffalo (Bos bubalis) to study the effect of feeding wheat straw presoaked with water on the voluntary feed intake, digestibility coefficients of nutrients and volatile fatty acid concentration and production. The feed intake was improved significantly (P < 0-05) in both the species as a result of soaking. The digestibility of crude protein and crude fibre was depressed (P < 0-05), whereas the nitrogen-free extract utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…The lignification of the paspalum hay and its tensile strength would be different from that of cereal straw. This may explain the greater response in the present experiment than in that of Chaturvedi et al (1973). The infusion of water directly into the rumen of the sheep did not increase their intake of hay, suggesting that palatability was a major effect.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The lignification of the paspalum hay and its tensile strength would be different from that of cereal straw. This may explain the greater response in the present experiment than in that of Chaturvedi et al (1973). The infusion of water directly into the rumen of the sheep did not increase their intake of hay, suggesting that palatability was a major effect.…”
Section: Resultscontrasting
confidence: 54%
“…The addition of water to the chaffed hay increased the feed intake by 19-5% in the absence of urea and 20-8% if added to the chaffed hay sprayed with urea, showing that the effects of water and urea were additive. Chaturvedi, Singh & Ranjhan (1973) found that the intake of watersoaked chaffed wheat straw was 8-4 % greater than that of dry straw. The lignification of the paspalum hay and its tensile strength would be different from that of cereal straw.…”
Section: Resultsmentioning
confidence: 95%
“…Sen et al 62 noted that buffaloes consumed more dry matter than cattle of similar age and body weight. Chaturvedi et al 63 did not find any significant difference in DMI of cattle and buffaloes. Ranjhan and Krishnamohan2 observed that consumption of dry matter by buffaloes as compared with cattle was between 73.1 to 116.9%.…”
Section: Resultsmentioning
confidence: 85%
“…Estimations of VFA production rates VFA production rates were estimated by the single-injection isotope-dilution technique as described previously (Chaturvedi, Singh & Ranjhan, 1973).…”
Section: E X P E R I M E N T a Lmentioning
confidence: 99%
“…The samples were freed of large particulate matter using specially-buiIt probes covered with fine nylon gauge as described previously (Chaturvedi et al 1973). …”
Section: Preparation Of Labelled Mixed Bacteriamentioning
confidence: 99%